2018
DOI: 10.15408/kauniyah.v11i1.5668
|View full text |Cite
|
Sign up to set email alerts
|

APLIKASI MARKA SSR PADA KEANEKARAGAMAN GENETIK DURIAN (Durio zibethinus Murr.) DI KABUPATEN DELI SERDANG, SUMATRA UTARA

Abstract: Kabupaten Deli Serdang merupakan salah satu kontributor untuk produksi durian (Durio zibethinus Murr.) Provinsi Sumatra Utara. Durian Deli Serdang memiliki varietas yang banyak dikenal di pasar buah domestik, diantaranya; Bintana, Ginting, dan Sikapal. Pada penelitian ini, dilakukan analisis keanekaragaman genetik pada durian asal Deli Serdang untuk memperoleh informasi keragaman genetik dan hubungan antar aksesi dengan menggunakan 6 lokus Simple Sequence Repeats (SSR). Hasil menunjukkan bahwa 9 aksesi durian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Marker amplification with the 3 SSR primers showed a polymorphic band. Polymorphism or allelic diversity resulting from a molecular marker is an illustration of the diversity or variation that occurs in each gene [29]. All markers had a product length of around 100 -250 bp.…”
Section: Analysis Of Molecular Markers Associated With Amylose Traits...mentioning
confidence: 99%
“…Marker amplification with the 3 SSR primers showed a polymorphic band. Polymorphism or allelic diversity resulting from a molecular marker is an illustration of the diversity or variation that occurs in each gene [29]. All markers had a product length of around 100 -250 bp.…”
Section: Analysis Of Molecular Markers Associated With Amylose Traits...mentioning
confidence: 99%
“…Past studies reported that the CTAB method was most suitable for isolating plant DNA containing high polysaccharides and polyphenols (Turaki et al, 2017). DNA isolation using the CTAB method has also succeeded in other species of the family Malvaceae (Hafizah et al, 2018). Eight accessions of the C. pentandra from West Sumatra incur successful amplifications using ITS1 and ITS4 primers at 54 °C annealing temperatures.…”
Section: Profile Of Its Sequence In C Pentandramentioning
confidence: 99%
“…The use of RAPD markings for the analysis of the genetic diversity of durian plants has been widely done, including in durian breadfruit [5], durian from Jepara [8] durian crossed [9] and several durian clones from West Java [10]. In some regions of North Sumatra, research has been conducted on durian diversity using SSR markings [11] and on Nias Island using SSR markings [3] but rapd markings have never been done.…”
Section: Introductionmentioning
confidence: 99%